PENGARUH K-POP BRAND AMBASSADOR TERHADAP LOYALITAS KONSUMEN: Studi Pada Pengguna Shopee - Chairunnisa Nurul Maulida; Arina Dieni Kamila (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Tadulako, 2021)
Korean culture is currently growing rapidly and expanding globally. It's existence tends to be accepted by public from various circles, resulting in a phenomenon of